Optimalisasi SDM dalam Pengembangan Model Kinerja Guru Berbasis PDCA di SMA Negeri 1 Baitussalam - Nursalami Nursalami; Riyan Tarida Maulana (Jurnal Ilmiah Guru Madrasah, 2025)
Effective human resource management (HRM) is necessary to ensure that teachers' competencies, motivation, and performance are in line with curriculum requirements and developments. However, teacher performance management in some schools is still administrative in nature, unstructured, and lacks follow-up. At Baitussalam 1 Public High School, teacher evaluation and guidance are not yet fully optimal, so that the utilization of potential and improvement of learning quality are not yet sustainable. This study aims to analyze the optimization of HRM in developing a PDCA (Plan-Do-Check-Act) based teacher performance model. The method used is descriptive qualitative with the subjects being the principal, teachers, and curriculum staff. Data were collected through interviews, observations, and documentation, then analyzed through data reduction, presentation, and verification. The results showed that the implementation of PDCA-based HRM has been structured, but there are still obstacles such as time constraints, differences in competence, facilities, motivation, and coordination. Optimization strategies were carried out through proper planning, systematic implementation, periodic evaluation, follow-up improvements, and increased teacher motivation. Consistent implementation of this model has been proven to support continuous improvement in teacher performance.